Specificity of Journalistic Texts on Economic Topics in the German Language Compared to Bulgarian Texts - Vasileva, Silvia (Research Papers, 2020)
The article presents research work on the similarities and differences of Bulgarian and German economic journalistic texts. It starts by analysing textlinguistic models to determine the kind, type, and genre of the text and focuses on those which are defined by the function of the text and the way the topic is developed. At the same time the problem of "specialized text" and its percentage has been solved. The constituent elements of "specializedness" are revealed in detail: terminology, non-terminology specialized vocabulary, and various lexico-semantic features. Depending on the topic development the texts are grouped into descriptive, descriptive with explicative elements, argumentative and argumentative-explicative, which are comparable according to a textlinguistic model in both languages.
Keywords: German economic journalistic texts; Textlinguistic models; Function; New textlinguistic model